2014
DOI: 10.1091/mbc.e14-04-0867
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway of rapid TLR-triggered activation of integrin-dependent leukocyte adhesion that requires Rap1 GTPase

Abstract: TLR2 and TLR5 ligation directly induces β2-integrin activation, promoting cell adhesion to ICAM-1. Systemic in vivo administration of the TLR2 ligand Pam3CSK4 increases integrin-dependent adhesion to endothelium within minutes. The signaling pathway linking TLR ligation with β2-integin activation involves Rac-1, NADPH oxidase 2, and Rap1-GTPase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Recent experimental findings summarized in the present review have identified and added new players in the cascade of neutrophil recruitment, which have increased the complexity of this process. The identification of TLR signalling as a regulator of neutrophil integrin activation has enhanced the repertoire of factors triggering neutrophil recruitment [23, 24]. The recently emerged role of α3β1 integrin for neutrophil recruitment in sepsis [42] supports the existence of different subsets of neutrophils and the idea that these cells may respond differently to inflammatory insults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental findings summarized in the present review have identified and added new players in the cascade of neutrophil recruitment, which have increased the complexity of this process. The identification of TLR signalling as a regulator of neutrophil integrin activation has enhanced the repertoire of factors triggering neutrophil recruitment [23, 24]. The recently emerged role of α3β1 integrin for neutrophil recruitment in sepsis [42] supports the existence of different subsets of neutrophils and the idea that these cells may respond differently to inflammatory insults.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, TLR2 and TLR5 ligation rapidly induces activation of leukocyte integrins and neutrophil adhesion to ICAM1 [24]. This pathway was dependent on activation of Rap1 GTPase, which is a well-established player in inside-out signal activation of integrins [4, 26, 27]; increased Rap1 activity was mediated by Rac1 activation, and NADPH oxidase 2-dependent reactive oxygen species production [24]. Such a mechanism for TLR-dependent neutrophil infiltration may be operative in graft-versus-host disease, whereby intestinal neutrophil recruitment is triggered by local microbial flora in a manner dependent on neutrophil TLRs [28].…”
Section: Novel Regulatory Mechanisms Of Neutrophil Adhesionmentioning
confidence: 99%
“…Besides chemokines and PSGL-1-ligation, Toll-like receptors also induce integrin activation (Harokopakis et al, 2006; Harokopakis and Hajishengallis, 2005). Recently, Toll like receptor 2 (TLR2)- and Toll like receptor 5 (TLR5)-ligation was shown to rapidly activate integrin-dependent leukocyte adhesion to immobilized intercellular cell-adhesion molecule 1 (ICAM-1) or fibronectin through activation of a pathway requiring Rac1, NADPH oxidase 2-mediated reactive oxygen species production and activation of Rap1-GTPase (Chung et al, 2014). Furthermore, TLRs activate via Ras the PI3K isoform p100γ, which then promotes activation of the α4β1-integrin (Schmid et al, 2011).…”
Section: The Leukocyte Adhesion Cascadementioning
confidence: 99%
“…In neutrophils, PTX3 is constitutively stored in specific granules and can be released locally at the neutrophil-endothelial cell interface in response to pro-inflammatory cytokines or triggered by Toll-like receptor agonists [159]. Toll-like receptor activation may therefore not only promote integrin activation and neutrophil recruitment [160], but through the secretion of PTX3 may also initiate a negative feedback loop. In particular, PTX-3 was shown to bind P-selectin on activated endothelial cells, thereby blocking P-selectin interaction with its leukocyte ligand PSGL-1, hence blocking neutrophil rolling on the endothelium under shear stress [133].…”
Section: Endogenous Regulators Of Neutrophil Recruitment To the Pementioning
confidence: 99%